2018
DOI: 10.5200/sm-hs.2018.010
|View full text |Cite
|
Sign up to set email alerts
|

Besimokanti Organizacija Šiuolaikinio Viešojo Valdymo Kontekste

Abstract: Vertinant Besimokančios organizacijos bruožų raišką šiuolaikinio viešojo valdymo kontekste ir remiantis Karen E. Watkins ir Victoria J. Marsick sudarytu klausimynu [30], 2017 m. sausio – kovo mėn. atliktas tyrimas viešojoje ambulatorinėje asmens sveikatos priežiūros įstaigoje, apklausti 228 darbuotojai. Daugelyje viešojo sektoriaus organizacijų veiklos vadyba, vertinimas ir rezultatų analizė tampa vis svarbesne viešojo sektoriaus institucijų veiklos sudedamąja dalimi. Viešojo sektoriaus organizacijoms, siekian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…It is important to emphasize that in the aspect of business competitiveness and work effectiveness, only the improvement of the whole organization is effective rather than one-time solutions (Blodgood & Salisbury, 2001;Welo & Ringen, 2018). For example, a research conducted by Skrickienė et al (2018) evaluated the education and training on an organizational level as the most effective, group and team level education as less effective and individual education as least effective. Unfortunately, the research indicated that employees educated and developed themselves primarily based on their own decision, as their organisations often did not provide them with sufficient motivations and stimuli (Schlechter et al, 2014;Hoole & Hotz, 2016;Tansley et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is important to emphasize that in the aspect of business competitiveness and work effectiveness, only the improvement of the whole organization is effective rather than one-time solutions (Blodgood & Salisbury, 2001;Welo & Ringen, 2018). For example, a research conducted by Skrickienė et al (2018) evaluated the education and training on an organizational level as the most effective, group and team level education as less effective and individual education as least effective. Unfortunately, the research indicated that employees educated and developed themselves primarily based on their own decision, as their organisations often did not provide them with sufficient motivations and stimuli (Schlechter et al, 2014;Hoole & Hotz, 2016;Tansley et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to remain attractive organizations, leisure service organizations must constantly improve, learn, and become creatively new -modern organizations. According to L. Skrickienė, D. Čepuraitė & K. Štaras (2018), modern public management means looking ahead, thinking about the future, how to turn from a traditional, today's organization into a constantly learning, developing, changing organization that meets the needs of society.…”
Section: The Theoretical Essence Of a Modern And Socially Responsible...mentioning
confidence: 99%
“…This is what defines a modern/learning organization and having these features, modern public management provides excellent opportunities to be successful. According to Skrickienė, Čepuraitė, Štaras (2018), the very approach to managing organizations is important. And this approach must be integral, defining the formula of flawless activity, which combines the theories of quality management and education, management, and health science (Skrickienė, Čepuraitė, Štaras, 2018).…”
Section: The Theoretical Essence Of a Modern And Socially Responsible...mentioning
confidence: 99%
“…Analizuojant Lietuvoje atliktus tyrimus, pastebima, kad organizacijų vadovai deklaratyviai akcentuoja mokymosi naudą, efektyvumą, besimokančių darbuotojų palaikymą ir skatinimą, taip sudarant palankias sąlygas profesiniam tobulėjimui, o vadovai besimokančioje organizacijoje išryškėja kaip besimokantys lyderiai, strategai, planuotojai bei asmenybės (Skrickienė, Čepuraitė, Štaras, 2018). Tačiau pastebimas ir vis didesnis polinkis į paviršutiniškumą ir vis labiau didėjančio modernumo ir aukštos kokybės imitavimo tendencija įvairiose žmogiškųjų išteklių ugdymo grandyse: orientacija į "išoriškai" šiuolaikišką ugdymą, kai siekiama ne tiek kokybiško ugdymo, kiek "išoriškai" įspūdingų teigiamų vertinimų (Melnikas, Jakubavičius, Leichteris, Stumbrytė, 2017).…”
Section: Lyderystės Raiškos Besimokančioje Organizacijoje Galimybių Nunclassified